2021
DOI: 10.31235/osf.io/fg6cy
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Non-parental care in childhood and adult outcomes: double whammy for minority children?

Abstract: BackgroundChildren who spent time in non-parental care report poor outcomes in many aspects of their later lives on average, but less is known about differences by ethnicity. We examined whether the health, socioeconomic, family, and living arrangements of adults who had been in non-parental care across the first three decades of adult life varied by ethnicity (White, Black, South Asian).MethodsWe used longitudinal data from the Office for National Statistics Longitudinal Study (LS). Participants were aged&a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Those exiting from residential care or with a history of placement instability had the poorest mental health outcomes. Studies suggested a possible connection between particular care types and psychosocial difficulties, as has been noted in international literature (Sacker et al, 2021).…”
Section: Improving Stability and Connectedness While In Carementioning
confidence: 57%
See 1 more Smart Citation
“…Those exiting from residential care or with a history of placement instability had the poorest mental health outcomes. Studies suggested a possible connection between particular care types and psychosocial difficulties, as has been noted in international literature (Sacker et al, 2021).…”
Section: Improving Stability and Connectedness While In Carementioning
confidence: 57%
“…Young people transitioning from out-of-home care (OOHC), often called care leavers, are recognised globally as a vulnerable group due to their often traumatic experiences prior to entering care, the varied quality and stability of care placements offered and the accelerated transition to independent adulthood that many encounter irrespective of their developmental needs and capacity (OECD, 2022). As a result, they may experience life-long inequalities and disadvantages compared to their non-care peers (Sacker et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in the US, it has been known for many years that Black children are disproportionately involved in the child welfare system (Dettlaff and Boyd, 2022). Sacker et al, 2021, andsee Achdut et al, 2023 for a recent international review and longitudinal study in Israel of long-term employment outcomes for care-leavers. Murray et al, 2020;Batty et al, 2022;Sacker et al, 2022.…”
Section: Discussionmentioning
confidence: 99%
“…Care leavers are regarded globally as a vulnerable group. They often experience long‐term social exclusion and inequalities compared with their non‐care peers (OECD, 2022; Sacker et al, 2021). Australian research has found that many care leavers have limited ongoing participation in education; exit care directly into homeless service systems and/or endure ongoing housing instability; spend time in the criminal justice system; or for those who are Aboriginal or Torres Strait Islander experience disconnection from culture and community (Beauchamp, 2016; McDowall, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the quality and stability of placements offered within the OOHC system vary greatly, and whilst some children are effectively supported to recover from their earlier traumas, others do not receive adequate care. On balance, those who have been placed in kinship care do best followed by those in foster care, and those in residential group home care have the poorest outcomes (Sacker et al, 2021).…”
mentioning
confidence: 99%